Inflammatory Effects of Blood–Air Interface in a Porcine Cardiopulmonary Bypass Model. Issue 1 (January 2020) - Carr, Benjamin D.; Johnson, Thomas J.; Gomez-Rexrode, Amalia; Mohammed, Azmath; Coughlin, Megan; Toomasian, John M.; Rojas-Pena, Alvaro; Bartlett, Robert H.; Haft, Jonathan W.
Abstract : Cardiopulmonary bypass (CPB) causes a systemic inflammatory response syndrome (SIRS) associated with multiorgan injury. A model was developed to test whether a blood–air interface (BAI) in the CPB circuit causes blood element activation and inflammation. Ten healthy swine were placed on partial CPB for 2 hours via the cervical vessels and monitored for 96 hours postoperatively. Five pigs (control group) had minimal air exposure in the circuit, while five were exposed to a BAI simulating cardiotomy suction. There were no significant differences in bypass flow or hemodynamics between the groups. In the BAI group, there was an increase in hemolysis after bypass (plasma-free hemoglobin 5.27 ± 1.2 vs. 0.94 ± 0.8 mg/dl; p = 0.01), more aggressive platelet consumption (28% vs. 83% of baseline; p = 0.009), leukocyte consumption (71% vs. 107% of baseline; p = 0.02), and increased granulocyte CD11b expression (409% vs. 106% of baseline; p = 0.009). These data suggest the inflammatory pattern responsible for the CPB-SIRS phenomenon may be driven by blood–air interaction. Future efforts should focus on BAI-associated mechanisms for minimizing blood trauma and inflammation during CPB.